Alterações laríngeas, sintomas vocais e aspectos autorreferidos de estresse em professores do ensino público - Crespo, Cassio Caldini (2009)
Aim: To analyze and correlate the occurrence of laryngeal changes, voice/throat symptoms and self-referred aspects related to stress under elementary and secondary public school teachers Justification: The vocal disorders affect each and every working class, however, they assume vital importance and are highly incapacitating to the ones who use their voices as a work tool, such as teachers. Stress is present on a regular daily basis of scholastic work due to various social factors as well as modern work relations. In this context, where vocal disorders (materialized in voice symptoms and in laryngoscopic images) combine with the daily reality of teachers who face stress often enough in their jobs, this current research has been conducted. Theoretical and methodological aspects: The research was based on an observational transversal prospective study. Data was collected and analyzed taking into account the evaluation of 58 teachers in two elementary and secondary municipal schools in Sorocaba/SP, which fulfilled the proposed criteria of inclusion and exclusion. The teachers were submitted to: (1) self assessment questionnaire on organizational questions, including questions about inference from stress and violence in the school environment and from voice/throat symptoms, called "Conditions of the Teacher s Vocal Production CPV-P", which examined organizational issues, including the inference with the stress and violence in the school environment and voice and throat symptoms; (2) Larynx examination by image, consisting of a video-nasal laryngoscopy, registered in digital media for further analysis and classification of existing alterations, by professional doctors in the area of otolaryngology. Statistical analysis of data were employed: the Pearson s Correlation, ANOVA-Analysis of Variance Test and the test of Association Chi-Square were used. Results: From the sample, 70.68% of subjects referred to, at least, one voice symptom. The ones which highest prevalence were: hoarseness, weak voice and flaws in the voice. At least one throat symptom was referred by 91.40% of subjects and the most prevalent were: phlegm, effort and fatigue to talk. During the image evaluation 91.37% of subjects showed at least one kind of disorder: evidence of laryngopharyngeal reflux in 68.97%, supra-glottic constriction in 65.52%, vocal cleft in 27.56%, and mass lesion in 32.75%. The results showed tendency of teachers with higher inference to stress the greater number of symptoms present in the throat, this does not occur with the vocal symptoms. There was no correlation between level of stress and laryngoscopy changes